Germinable seed bank of grasses in the caldenforests before and after dispersal differences (Semiárida, 2020)
The seed bank is a pool of viable mature seeds ready to germinate on the soil surface or buried plant residues. The composition and size of the seed bank rapidly fluctuates depending on the input and seed losses. The aim of this study was to compare the viable seed bank of grasses before fruiting (October 2008) and after the spread of caryopsis (March 2009), after performing a prescribed burning and a subsequent grazinng. Delimited 5 patches dominated by forage grasses, 5 dominated by non forage and 5 shrub. In each patch were collected 5 samples of soil using a metal cylinder at various depth. It was used the seed bank seedling emergence method. We identified 8 grasses: 5 forage, Piptochaetium napostaense, Poa ligularis, Bromus catharticus v. rupestres, Hordeum stenostachys and Setaria pampeana and 3 non forage: Jarava ichu, Nassella tenuísima and Nassella trichotoma. The results indicate a higher germination of forage after the spread of caryopses at the expense of non-fodder, indicating a possible recovery of the pasture.
Keywords: propagules; grazing; fire; caldén forest